(untitled) (Bangladesh Journal of Child Health, 2023)
Background: Type 2 diabetes (T2D) has become a serious health problem in children and adolescents as the prevalence of obesity is increasing. Objective: To observe the baseline clinical and laboratory findings and treatment modalities of children and adolescents with newly diagnosed T2D. Materials & Methods: This cross-sectional study was done from Jan- Dec.2017 in Changing Diabetes in Children (CDiC), Paediatric diabetes OPD clinic in BIRDEM among newly diagnosed T2D children and adolescents. Results: Among 68 patients majority were female (64.7%). Mean age was 13.1 ± 2.5 years. Ten patients were below 10 years. Most of the patients were from urban & semi urban area and high to middle socioeconomic status. Family history was present in 91.2% and 22.1 % mother had H/O GDM. Forty two patients (61.8%) had typical and 22 (32.3%) had atypical symptoms. Thirty seven children had acanthosis nigricans (54.4%). Majority were found overweight (53/68), and (12/68) were obese. Mean HbA1c was 10.2 ± 2.8. Life style modification was advised to all. Insulin was started along with metformin in patients with high HbA1c and 33.8% patients were given metformin only. While comparing, BMI was found high in basal and metformin group. Lower fasting blood glucose and HbA1c were observed in patients with metformin only. Conclusion: T2D is emerging in children and adolescents. The screening of children at high risk of T2D is essential for preventive and timely remedial measures. BANGLADESH J CHILD HEALTH 2022; VOL 46 (1) : 9-13